2021
DOI: 10.1111/jfbc.14003
|View full text |Cite
|
Sign up to set email alerts
|

A review of some common African spices with antihypertensive potential

Abstract: Hypertension is the most common non-communicable disease, with about 1.28 billion hypertensive people worldwide. It is more prevalent in men than women and more common in the elderly. Hereditary, age, obesity, lifestyle, diet, alcohol, and chronic metabolic diseases are the major risk factors of hypertension. Treating hypertension is a complex process as there are several mechanisms responsible for its pathogenesis; hence, a combination of several drugs is used for managing hypertension. Drugs used in managing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Use of traditional medicine (TM) is widespread in sub-Saharan Africa as a treatment option for a wide range of disease, 4 including for the management of hypertension. 5–7 TM encompasses different types of healthcare practices. 8 According to a recent systematic review, in sub-Saharan Africa, the most common form is biological-based (use of medicinal herbs and plants, homeopathy), followed by faith-based (prayer, spirituality), and mind–body therapies (eg, massage, meditation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of traditional medicine (TM) is widespread in sub-Saharan Africa as a treatment option for a wide range of disease, 4 including for the management of hypertension. 5–7 TM encompasses different types of healthcare practices. 8 According to a recent systematic review, in sub-Saharan Africa, the most common form is biological-based (use of medicinal herbs and plants, homeopathy), followed by faith-based (prayer, spirituality), and mind–body therapies (eg, massage, meditation).…”
Section: Introductionmentioning
confidence: 99%
“…Use of traditional medicine (TM) is widespread in sub-Saharan Africa as a treatment option for a wide range of disease,4 including for the management of hypertension 5–7. TM encompasses different types of healthcare practices 8.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the observation that treated rats showed more excellent S-allyl-L-cysteine cystathionine c-lyase activity in the left ventricles and higher levels of H 2 S in plasma-controlling treated animals (Seki & Hosono, 2015). Studies have also suggested that garlic and SAC showed cardioprotective effects and vasodilators affecting CSE activity and H 2 S production (Adeoye et al, 2022;Citi et al, 2021).…”
Section: Garlic Enhances Hydrogen Sulphide Productionmentioning
confidence: 99%
“…It is based on the observation that treated rats showed more excellent S ‐allyl‐ l ‐cysteine cystathionine c‐lyase activity in the left ventricles and higher levels of H 2 S in plasma‐controlling treated animals (Seki & Hosono, 2015). Studies have also suggested that garlic and SAC showed cardioprotective effects and vasodilators affecting CSE activity and H 2 S production (Adeoye et al., 2022; Citi et al., 2021). It is proposed that reducing the dependent H 2 S blood pressure is mainly mediated through the potassium‐sensitive sulfhydration channel (kATP) that promotes the relaxation of the sensitive channel of vascular smooth muscle cells.…”
Section: Garlic Enhances Hydrogen Sulphide Productionmentioning
confidence: 99%
See 1 more Smart Citation